The Impact of Bilateral Trade Between China and The Philippines on Trade and Economic Growth: A Simultaneity Approach - Huang, Wei; DIZON, RICARDO L. (Journal of Theory and Practice in Economics and Management, 2025)
This study investigated the effect of a bilateral agreement between the Philippines and China, which commenced last 1992 on Philippine export trade to China, and examined the impact of the export of the Philippines to China on the economic growth of the Philippines. The paper used a combination of the instrumental variable method and dummy variable to investigate the simultaneity relationship between the dummy variable of a bilateral agreement between the Philippines and China and the export trade of the Philippines to China and its simultaneous ties to the country’s economic growth.